Thinking maps in moral education - Balakrishnan, Vishalache (2014)
Since the launch of the Blue Print for Education in Malaysia (2013-2025), various transformation strategies have been introduced in the Ministry of Education in Malaysia. Some programmes are local such as upgrading the teaching profession, encouraging the crème of the crème of the younger generation to pursue the teaching profession and others. At a more international level, various teaching methodologies have been imported and introduced to encourage higher order thinking skills (HOTS) among teachers to be taught to students in primary and secondary schools. One of the technique introduced stage by stage and finally nationwide on 1 April 2014 was using i-THINK maps in teaching and learning. This article describes the history of introducing i-THINK maps in the education system in Malaysia, especially in Moral Education, the issues involved and the way forward.